Performance test of organic planting bags for woody plant seedlings - Lutfi, Musthofa; Nugroho, Wahyunanto Agung; Vo, Huy Thanh; Djoyowasito, Gunomo; Ahmad, Ary Mustofa; Sandra, Sandra (International Journal of Agricultural and Biological Engineering, 2020)
Organic planting bag has been developed to overcome both weaknesses of plastic polybags, contaminating the soil and damaging the plant’s root when transplanting. The improvement in this stage was achieved by inserting coconut fiber to strengthen a bag. The main purpose of this study was to investigate the effectiveness of seedling and transplanting by using organic planting bags, employed, three woody plants, i.e., Albizia (Albizia julibrissin), Cadam (Neolamarckia cadamba) and Gmelina (Gmelina arborea). Performance testing of organic plant bags was conducted on three compositions of coconut fiber and water hyacinth. Two stages of experiments were conducted to know bag performance. First, the testing of organic plant bags during the nursery was conducted for 50 d from day 0 to day 50. Second, the testing of organic plant bags after transplanting and observed on days 60, 70, and 80, after transplanted on the field. The parameters in this study were plant height, a total of roots that penetrate the organic plant bags and a total of leaves and stem diameters of plant grown in the organic bag and transplanting on land. The results showed that organic planting bag with the composition 155 g of coconut fiber and 505 g of water hyacinth (A3B3) has 0.020 kg/cm2 compressive strength and provides the best plant growth rates. Compressive strength affects the number of roots which penetrate the organic bag. Generally, the growth of seed in organic bags is faster than that in polybags. Albizia shows a higher growth rate (0.379 cm/d) compared to Cadam and Gmelina.Keywords: seedling effectiveness, organic planting bag, nursery, transplanting, woody plantDOI: 10.25165/j.ijabe.20201305.4975Citation: Lutfi M, Agung N W, Vo T H, Djoyowasito G, Ahmad A M, Sandra S. Performance test of organic planting bags for woody plant seedlings. Int J Agric & Biol Eng, 2020; 13(5): 93–98.